2021
DOI: 10.1038/s41467-021-25961-1
|View full text |Cite
|
Sign up to set email alerts
|

The identification of grain size genes by RapMap reveals directional selection during rice domestication

Abstract: Cloning quantitative trait locus (QTL) is time consuming and laborious, which hinders the understanding of natural variation and genetic diversity. Here, we introduce RapMap, a method for rapid multi-QTL mapping by employing F2 gradient populations (F2GPs) constructed by minor-phenotypic-difference accessions. The co-segregation standard of the single-locus genetic models ensures simultaneous integration of a three-in-one framework in RapMap i.e. detecting a real QTL, confirming its effect, and obtaining its n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…The favorable allele for increased grain size and uniform shape is accumulated in elite germplasm because of directional selection during the domestication process (Gegas et al , 2010; Zhang et al , 2021). However, landraces that evolved from natural and human selection might still be a significant source of positive genetic diversity (Casañas et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The favorable allele for increased grain size and uniform shape is accumulated in elite germplasm because of directional selection during the domestication process (Gegas et al , 2010; Zhang et al , 2021). However, landraces that evolved from natural and human selection might still be a significant source of positive genetic diversity (Casañas et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In DongLanMoMi rice, several purple pericarp-related genes, such as LOC_Os02g49140, LOC_Os12g07690, and LOC_Os06g17020, were identified as candidate genes for anthocyanin biosynthesis following an analysis of F 2 progeny using the new Pair-wise Comparison Analysis for Multiple Pool-seq (PCAMP) method (Yang et al, 2019). Additionally, the recently developed Rapid multi-QTL Mapping (RapMap) method, which involves the construction of a series of F 2 gradient populations derived from multiple bi-parents with gradient phenotypes in diverse germplasms, was used to identify eight genes controlling the natural variations in rice grain length and width within 3 years (Zhang et al, 2021). The findings of the present study suggest two complementary genes regulate the green coloration of the pericarp of LM8 grains, which is in accordance with the results of earlier research.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of constructing RILs population, multiple generations of arti cial and natural selection are required, which leads to the increase of partial separation ratio of this population, which is also the reason for the highest partial separation ratio of this population (Elomaa et al, 2018). It has been reported that the proportion of partial separation between molecular markers is between 24.7% and 98.9% (Zhang et al, 2021). The proportion of partial separation in this study is 0%, which is relatively low, which may be related to the population type, crop species and the selection of mapping markers.…”
Section: Discussionmentioning
confidence: 99%